Patient-Reported Symptoms and Sequelae 12 Months After COVID-19 in Hospitalized Adults: A Multicenter Long-Term Follow-Up Study - Comelli, Agnese; Viero, Giulia; Bettini, Greta; Nobili, Alessandro; Tettamanti, Mauro; Galbussera, Alessia Antonella; Muscatello, Antonio; Mantero, Marco; Canetta, Ciro; Martinelli Boneschi, Filippo; Arighi, Andrea; Brambilla, Paolo; et al. (Frontiers in Medicine, 2022)
Objective Our knowledge on the long-term consequences of COVID-19 is still scarce despite the clinical relevance of persisting syndrome. The aim of this study was to analyze patient-reported outcomes, including assessment by specific questionnaires of health impairment and symptoms. Methods This is a prospective, observational and multicenter cohort study coordinated by Fondazione IRCSS Ca' Granda Ospedale Maggiore Policlinico di Milano and Istituto di Ricerche Farmacologiche Mario Negri IRCCS including eight hospitals located in North and Central Italy. A telephone interview to assess rehospitalization, access to health care resources, general health status subjective evaluation, and symptoms was performed at 12 months after the discharge in patients admitted to hospital because of COVID-19 from February 2020 to the end of May 2020. Results Among the 776 patients discharged alive, 44 (5.7%) died, 456 subjects (58.8%) completed the questionnaire and 276 (35.6%) were not reachable or refused to join the telephone interview. The mean age of the study population was 59.4 years (SD 14.1), 69.8% of individuals needed oxygen support during hospitalization and 10.4% were admitted to ICU. Overall, 91.7% of participants reported at least one symptom/sequela at 12 months. Exertional dyspnea (71.7%), fatigue (54.6%), and gastrointestinal symptoms (32.8%) were the most reported ones. Health issues after discharge including hospitalization or access to emergency room were described by 19.4% of subjects. Female and presence of comorbidities were independent predictors of whealth impairment and presence of ≥2 symptoms/sequelae after 12 months from hospitalization for COVID-19. Conclusions Patient-reported symptoms and sequelae, principally dyspnea and fatigue, are found in most individuals even 12 months from COVID-19 hospitalization. Long-term follow-up based on patient-centered outcome can contribute to plan tailored interventions.